2011
DOI: 10.1002/nur.20465
|View full text |Cite
|
Sign up to set email alerts
|

The moderating effect of sexual pressure on young Urban women's condom use

Abstract: The purpose of this study was to examine whether women's experiences of sexual pressure moderated the relationship between sexual empowerment determinants and condom use in a sample of 100 high-risk women, ages 19-25. Five sexual empowerment determinants of condom use were identified from the literature: HIV knowledge, self-esteem, condom self-efficacy, positive attitudes toward condom use, and condom negotiation skills. Linear and logistic regression analyses revealed that positive attitudes toward condom use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
1
7
0
1
Order By: Relevance
“…The study supports previous studies examining the difficulties women face in negotiating condom use such as passivity and unequal power dynamics in a sexual relationship 4 5. This study notably explored women's subjective experiences regarding condom use after being diagnosed with an STI.…”
Section: Commentarysupporting
confidence: 83%
“…The study supports previous studies examining the difficulties women face in negotiating condom use such as passivity and unequal power dynamics in a sexual relationship 4 5. This study notably explored women's subjective experiences regarding condom use after being diagnosed with an STI.…”
Section: Commentarysupporting
confidence: 83%
“…Pressure from a man to have sex without condoms has been identified as contributing to heterosexual women’s sexual decisions (4). Consistent with this, men have reported that exerting verbal pressure to forgo condoms is acceptable and normative; and that they have done so in the past and intend to do so in the future (5,6).…”
Section: Partner Pressure For Unprotected Sexmentioning
confidence: 99%
“…37 También se ha reportado que en mujeres de 19 y 25 años las actitudes positivas hacia el uso del condón y la negociación para su empleo son los mejores predictores de la utilización de ese anticonceptivo. 38 Adicionalmente, el presente estudio encontró una asociación entre la baja autoeficacia respecto al uso y la negociación del condón y tener necesidades insatisfechas en el tema de la anticoncepción. Asimismo, existen otras circunstancias asociadas al no uso de anticonceptivos durante las relaciones sexuales.…”
Section: Anticoncepción En Adolescentes Escolarizadosunclassified